Mineralization-defects are comparable in fluorotic impacted human teeth and fluorotic mouse incisors (2020)
Objective Fluoride excess of 0.05–0.07 mg F/kg bw/day in water or food additives like salt is the principal cause of endemic dental fluorosis. How fluoride causes these defects is not clear yet. Recent studies in rodents suggest that development of enamel fluorosis is associated with insufficient neutralization of protons released during the formation of hypermineralized lines. Design Here we examined whether hypermineralization could also be assessed by MicroCT in developing molar enamel of humans exposed to fluoride. Result Micro-CT analysis of hypomineralized enamel from human fluorotic molars graded by the Thylstrup–Fejerskov (TF) Index as III–IV showed weak hypermineralized lines and hypermineralized patches not seen in TF-I/II grade enamel. The mesio-distal sides of these molar teeth were significantly smaller (∼18%, p = 0.02) than in TF-I/II teeth. Conclusion The patterns of changes observed in human fluorotic teeth were similar to those in fluorotic rodent incisors. The data are consistent with the hypothesis that also in developing human teeth fluoride-stimulated local acidification of enamel could be a mechanism for developing fluorotic enamel.